Role of Latex Particle Agglutination Test in the Diagnosis of Meningitis (Bangladesh Journal of Medical Microbiology, 2016)
A total  of 45 clinically suspected  cases of meningitis  of all  ages,  admitted at Rajshahi Medical  College  Hospital(RMCH),  were  studied to  find  out the etiological  agents of meningitis. Among  the cases,  32 (7l.1oh)  were diagnosed  asaseptic  meningitis  and  L3 (ZS.Sgoh)  as  bacterial meningitis by the  conventional  CSF  study. But  out of total  45 cases,lg  (40oh) were diagnosed as bacterial  meningitis  by  Latex  particle  agglutination test (LPAT).  The  LPAT  is  widelyused in  clinical  microbiology laboratories  and can  be considered  as an important  supplement  to the  culture  andGram stain of CSF specimens. Rapid  antigen  detection  tests may  provide positive results  when  culture  and  Gramstain results  are  negative for  meningitis patients  who have  received antimicrobial  therapy.  So, in our country, where empirical  broad-spectrum antibiotic is  randomly  used, LPAT may  be considered  as an adjunct  to establish  thediagnosis  of  bacterial  meningitis.Bangladesh  J Med Microbiol  2007;01(01):10-12